2020
DOI: 10.3390/ijerph17041435
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Genotoxicity in Farmers and Laborers of Ecological and Conventional Banana Plantations in Ecuador

Abstract: Banana farming represents an important segment of agricultural production in Ecuador. The health of farmworkers might be compromised by the extensive use of pesticides in plantations applied under poorly regulated conditions. Due to an increased awareness of pesticide-related problems for nature, as well as for worker and consumer health, ecological farming has been established in some plantations of Ecuador. We set out to investigate the occupational health of workers in both conventional and ecological farmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
10
0
2
Order By: Relevance
“…This provided an opportunity to confirm the original results in different settings. In a first paper [33], we already confirmed the higher frequency of cytological anomalies in buccal cells of workers exposed to pesticides compared to controls. This paper was in agreement with our paper about workers from the D.R.…”
Section: Comparison With Our Previous Studysupporting
confidence: 60%
See 2 more Smart Citations
“…This provided an opportunity to confirm the original results in different settings. In a first paper [33], we already confirmed the higher frequency of cytological anomalies in buccal cells of workers exposed to pesticides compared to controls. This paper was in agreement with our paper about workers from the D.R.…”
Section: Comparison With Our Previous Studysupporting
confidence: 60%
“…We already presented our results of a cross-sectional medical survey in Ecuador regarding indicators of genotoxicity in conventional and ecological farming [33] where we clearly demonstrated higher frequencies of genotoxicity and cytotoxicity markers in buccal cells of the pesticide users compared to workers in organic farming. We provide here additional results from the same population, focusing on self-reported acute symptoms in conventional and ecological banana farmworkers.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is important to note that, while a substantial number of papers was identified in the present review, there is in fact a relative paucity of research in this field, considering that cancer is one of the principal risks to human health, and is known to be associated with occupational exposure to pesticides, an increasing problem worldwide, in addition to its association with other comorbidities (Brust et al 2019 ; Jacobsen-Pereira et al 2020 ; Mongedet al 2020 ). Even when convincing evidence is presented, the procedures used to confirm this association and its determining factors are often not dealt with adequately (Elebead et al 2012 ; Tual et al 2013 ; Jin et al 2017 ; Tarar and Riaz 2019 ; Hutter et al 2020 ). Kachuri et al ( 2017 ) observed that exposure to pesticides may lead to an increase in hematopoietic cancers, whereas increased risks of lip cancer and melanoma may be attributed to exposure to the sun.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note here that the monitoring of exposure to xenobiotics, such as pesticides, using biomarkers like the micronucleus test, is an essential tool for the early detection and prevention of diseases such as oral cancer (Tomiazzi et al 2018 ). Another factor limiting the conclusions of a toxicological or genotoxic analysis is the timing of the testing, which means that it may not always be possible to link the results with the specific components of a pesticide, which is an important question, given that the mixing of pesticides is a common practice (Hutter et al 2020 ; Ramos et al 2021 ). This represents an additional problem with the application of questionnaires, given that almost half of the farm workers do not know which pesticides they have been exposed to (Vindas et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%